Persia to China: the Silk Road of Restorative Justice I - Braithwaite, John (Asian journal of criminology, 2017)
This paper to the 2016 Beijing meeting of the Asian Criminological Society is the first of two lectures on the theme of The Silk Road of Restorative Justice. The second is the annual lecture of the European Forum for Restorative Justice held jointly with the Asia-Pacific Forum for Restorative Justice in Milan (Braithwaite 2017). This first paper opens the idea of restorative justice as a way of thinking that flows back and forth along the Silk Road with a special focus on the development of relational, republican, and feminist thought in ancient and modern China and Persia. Both contemporary China and Iran are left today with quite a universal yet modest national policy of support for restorative justice. Some co-optation of restorative justice by the state and disengagement from it by many key justice professionals are evident in both China and Iran. The second paper argues more normatively for openness to hybridity along the Silk Road. It identifies virtues of being a republican-socialist-capitalist-feminist advocate of restorative justice in light of what we learn along the Silk Road. The unifying message of both papers is that excellence in restorative justice is nurtured by travelling many roads in search of helpful hybrids.